2021
DOI: 10.1177/03331024211046618
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of hypothalamic functional changes in migraine patients

Abstract: Objective To elucidate the hypothalamic involvement in episodic migraine and investigate the association between hypothalamic resting state functional connectivity changes and migraine patients’ clinical characteristics and disease progression over the years. Methods Ninety-one patients with episodic migraine and 73 controls underwent interictal resting state functional magnetic resonance imaging. Twenty-three patients and controls were re-examined after a median of 4.5 years. Hypothalamic resting state functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…Russo et al [45] found by thermal stimulation of the trigeminal nerve in the maxillary region that the activity in the higher visual processing areas, including the lingual gyrus, increased in patients with migraine with aura compared with HC and those with migraine without aura. Messina et al [46] found that the functional connectivity between the right hypothalamus and ipsilateral lingual gyrus decreased in patients with migraine compared with HC, and was associated with a higher frequency of migraine attacks. The lingual gyrus is associated with psychiatric disorders such as depression, anxiety, and panic attacks [47,48].…”
Section: Compared With the Baseline The Dalff Values Decreased In Tri...mentioning
confidence: 99%
“…Russo et al [45] found by thermal stimulation of the trigeminal nerve in the maxillary region that the activity in the higher visual processing areas, including the lingual gyrus, increased in patients with migraine with aura compared with HC and those with migraine without aura. Messina et al [46] found that the functional connectivity between the right hypothalamus and ipsilateral lingual gyrus decreased in patients with migraine compared with HC, and was associated with a higher frequency of migraine attacks. The lingual gyrus is associated with psychiatric disorders such as depression, anxiety, and panic attacks [47,48].…”
Section: Compared With the Baseline The Dalff Values Decreased In Tri...mentioning
confidence: 99%
“…In a selective group of migraine with aura patients, who always had side-fixed aura symptoms, hyperexcitability was reported in the symptomatic hemisphere during the asymptomatic phase [17]. The application of fMRI techniques to study asymptomatic migraine patients has also recently provided new insights into imaging prognostic markers for migraine disability and severity [16,18]. Future larger studies are needed to confirm these findings.…”
Section: Imaging In the Asymptomatic Phase Of Migrainementioning
confidence: 99%
“…Other studies suggested that functional brain alterations might be dynamic, as they change according to migraine severity [12]. The functional interplay between the hypothalamus and other brain regions may be implicated in pain and visual processing changes over time according to patients’ clinical features [16]. In a selective group of migraine with aura patients, who always had side-fixed aura symptoms, hyperexcitability was reported in the symptomatic hemisphere during the asymptomatic phase [17].…”
Section: Imaging In the Asymptomatic Phase Of Migrainementioning
confidence: 99%
“…Melatonin is an endogenous hormone responsible for the regulation of the sleep-wake cycle and other circadian rhythms [100], and it is pharmaceutically available for the treatment of insomnia. Given the relationship between migraine and sleep [101], and the postulated role of the hypothalamus in migraine [102], melatonin has been suggested to have Post-hoc analysis of [65,66] Single attack Increased rates of normal function and treatment satisfaction in those with an insufficient triptan response previously compared with placebo a therapeutic role in migraine for several years. Its antinociceptive role has been suggested as occurring through a variety of receptor systems, including the μ opioid and GABA-B receptors [103], as well as the possibility that it exerts a therapeutic effect on anxiety and sleep, causing a secondary impact on pain perception.…”
Section: Melatonin: Preventive Treatmentmentioning
confidence: 99%